2019
DOI: 10.20914/2310-1202-2018-4-254-258
|View full text |Cite
|
Sign up to set email alerts
|

The influence of fireweed powder on the quality of wheat bread

Abstract: This paper presents the results of studying the effect of dry-leaved Chamerion angustifolium (L.) Holub dry powder on quality indicators of wheat bread, in which part of the highest-grade wheat flour was replaced by 3, 5 and 10% of powder. The study showed that the addition of narrow-leaved powder in different amounts (3, 5 and 10% by weight of wheat flour) at the stage of cooking, the dough has a different impact on the quality indicators of the products. With the increase in the amount of the infusion of nar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…After the completion of baking process, the bread yield and baking losses were calculated. In addition, bread volume, crumb porosity [33], and bread acidity were estimated as previously described [34]. The loaf volume converted to 100 g of bread was determined using a 3D scanner (NextEngine, West Los Angeles, CA, USA) and calculated using a computer program (MeshLab, ISTI-CNR research center, Rome, Italy).…”
Section: Methodsmentioning
confidence: 99%
“…After the completion of baking process, the bread yield and baking losses were calculated. In addition, bread volume, crumb porosity [33], and bread acidity were estimated as previously described [34]. The loaf volume converted to 100 g of bread was determined using a 3D scanner (NextEngine, West Los Angeles, CA, USA) and calculated using a computer program (MeshLab, ISTI-CNR research center, Rome, Italy).…”
Section: Methodsmentioning
confidence: 99%
“…The volume of the loaf was determined using a 3D scanner (NextEngine, West Los Angeles, CA, USA) and calculated using a computer program (MeshlLab, ISTI-CNR Research Centre, Rome, Italy) and then converted into 100 g of bread [38]. The density of the bread crumb was determined from the mass of a sample of known volume [50].…”
Section: Yield Volume and Density Of Bread Crumbmentioning
confidence: 99%
“…The acidity of bread could be increased by adding different kinds of additives. One study showed that acidity of bread can be altered by the addition of crushed safflower seeds [45] or dry powder of Chamerion angustifolium (L.) Holub leaves [31]. Cistus incanus L. used in this study was characterized by ash content of 5.0±0.21%, and an addition of these herbs to bread resulted in significant changes in the ash content and color of the bread ( Table 1).…”
Section: Physical Properties Of Bread Fortified With Cistus Incanusmentioning
confidence: 88%
“…After the completion of baking process, the bread yield and baking losses were calculated. In addition, bread volume, crumb porosity [30], and bread acidity were estimated as previously described [31]. The loaf volume converted to 100 g of bread was determined using a 3D scanner (NextEngine, USA) and calculated using a computer program (MeshLab).…”
Section: Physical Properties Of Breadmentioning
confidence: 99%